Wet depositional fluxes of 7Be and 210Pb and their influencing factors at two characteristic cities of China. (May 2019) - Peng, Anguo; Liu, Guangshan; Jiang, Zhengming; Liu, Guoqing; Liu, Min
Abstract: The atmospheric depositional fluxes of 7 Be and 210 Pb in Yueyang and Hengyang were measured by the γ spectrum analysis method and their influencing factors were discussed. Results are summarized as follows: the variation ranges and average values of 7 Be depositional fluxes are very close to each other in the two characteristic sampling regions, but not for 210 Pb. In the same sampling region, there is a strong positive linear correlation between the depositional fluxes of two nuclides and their monthly variations are synchronous. Correlation coefficients between atmospheric depositional fluxes and different factors suggest that rainfall is the most important influencing factor, but in Hengyang sampling region, the source has great effect on the depositional fluxes of 210 Pb. Graphical abstract: The monthly variation of atmospheric depositional fluxes of 7 Be and 210 Pb in Yueyang and Hengyang sampling regions during 2012 and 2016 are showed in Fig. 1. It is obvious that the variation of depositional fluxes of these two nuclides with month are synchronous, which suggest that although the sources of 7 Be and 210 Pb were different, their removal process from the atmosphere are very similar.Image 1 Highlights: The variation range and average values of 7 Be depositional fluxes are very close to each other in these two regions, but not for 210 Pb. There is a strong linear correlation between 7 Be and 210 Pb. Rainfall is the most important factor. The source has great effect on 210 pb in Hengyang.